Reverse Translation in Tuberculosis: Neutrophils Provide Clues for Understanding Development of Active Disease - Dorhoi, Anca; Iannaccone, Marco; Maertzdorf, Jeroen; Nouailles, Geraldine; Weiner 3rd, January; Kaufmann, Stefan H. (Frontiers in Immunology, 2014)
Tuberculosis (TB) is a major health issue globally. Although typically the disease can be cured by chemotherapy and prevented – at least in part, in newborn by vaccination, general consensus exists that development of novel intervention measures requires better understanding of disease mechanisms. Human TB is characterized by polarity between host resistance as seen in 2 billion individuals with latent TB infection and susceptibility occurring in 9 million individuals who develop active TB disease every year. Experimental animal models often do not reflect this polarity adequately, calling for a reverse translational approach. Gene expression profiling has allowed identification of biomarkers that discriminate between latent infection and active disease. Functional analysis of most relevant markers in experimental animal models can help to better understand mechanisms driving disease progression. We have embarked on in-depth characterization of candidate markers of pathology and protection hereby harnessing mouse mutants with defined gene deficiencies. Analysis of mutants deficient in miR223 expression and CXCL5 production allowed elucidation of relevant pathogenic mechanisms. Intriguingly, these deficiencies were linked to aberrant neutrophil activities. Our findings point to a detrimental potential of neutrophils in TB. Reciprocally, measures that control neutrophils should be leveraged for amelioration of TB in adjunct to chemotherapy.